Ceramic on Metal Substrates Produced by Plasma Spraying for Thick Film Technology. (1983) - Gołonka, Leszek; Pawłowski, Lech
Abstract : The arc plasma spraying process was applied to obtain ceramic coatings on stainless steel substrates. The outer coatings were formed from pure alumina or alumina + 2 wt. % titania mixture. The nichrome intermediate coating was applied to increase adhesion of ceramic coating to stainless steel. The X-ray analysis, metallographic and SEM investigations of the sprayed coatings were also carried out. The effect of interaction of thick film conductor and resistor compositions was studied. Conductor ink P 202 PdAg and resistor ink DP 1321 were evaluated. The TCR, resistance stability were measured as a function of firing cycles. These parameters and the resistivity of sprayed alumina were compared with standard 96% alumina substrate characteristics.